Indigenous education through dance and ceremony : a Mexica palimpsest - Colín, Ernesto (Palgrave Macmillan's postcolonial studies in education., 2014)
In the first book on Aztec dance in the United States, Ernesto Colín combines cultural anthropology, educational theory, and postcolonial theory to create an innovative, interdisciplinary, long-term ethnography of an Aztec dance circle and makes a case for the use of the metaphor of palimpsest as an ethnographic research tool.